Strategies to Promote ResiliencY (SPRY): a randomised embedded multifactorial adaptative platform (REMAP) clinical trial protocol to study interventions to improve recovery after surgery in high-risk patients. Issue 9 (29th September 2020) - Reitz, Katherine Moll; Seymour, Christopher W; Vates, Jennifer; Quintana, Melanie; Viele, Kert; Detry, Michelle; Morowitz, Michael; Morris, Alison; Methe, Barbara; Kennedy, Jason; Zuckerbraun, Brian; Girard, Timothy D; et al.
Abstract : Introduction: As the population ages, there is interest in strategies to promote resiliency, especially for frail patients at risk of its complications. The physiological stress of surgery in high-risk individuals has been proposed both as an important cause of accelerated age-related decline in health and as a model testing the effectiveness of strategies to improve resiliency to age-related health decline. We describe a randomised, embedded, multifactorial, adaptative platform (REMAP) trial to investigate multiple perioperative interventions, the first of which is metformin and selected for its anti-inflammatory and anti-ageing properties beyond its traditional blood glucose control features. Methods and analysis: Within a multihospital, single healthcare system, the Core Protocol for Strategies to Promote ResiliencY (SPRY) will be embedded within both the electronic health record (EHR) and the healthcare culture generating a continuously self-learning healthcare system. Embedding reduces the administrative burden of a traditional trial while accessing and rapidly analysing routine patient care EHR data. SPRY-Metformin is a placebo-controlled trial and is the first SPRY domain evaluating the effectiveness of three metformin dosages across three preoperative durations within a heterogeneous set of major surgical procedures. The primary outcome is 90-day hospital-free days. Bayesian posterior probabilities guide interim decision-making with predefined rules to determine stopping for futility or superior dosing selection. Using response adaptative randomisation, a maximum of 2500 patients allows 77%–92% power, detecting >15% primary outcome improvement. Secondary outcomes include mortality, readmission and postoperative complications. A subset of patients will be selected for substudies evaluating the microbiome, cognition, postoperative delirium and strength. Ethics and dissemination: The Core Protocol of SPRY REMAP and associated SPRY-Metformin Domain-Specific Appendix have been ethically approved by the Institutional Review Board and are publicly registered. Results will be publicly available to healthcare providers, patients and trial participants following achieving predetermined platform conclusions. Trial registration number: NCT03861767 .